Uzupełnienie Równań Technicznej Teorii Powłok - Łukasiewicz, S. (Engineering Transactions, 1963)
This paper is devoted to the derivation of more accurate equations of the theory of non-shallow shells.The solution of the shell is reduced to that of a set of two equations (4.18) of which the form resembles those of Vlasov engineer's theory of shells.For circularly cylindrical shells these equations reduce to the equation proposed by Morley, [4]. The accuracy of this equation is verified by comparing it with Flügge's equation for the Cylindrical shell, very good agreement being found. For shells with double curvature the results obtained by means of the equations proposed are confronted with those of the Vlasov engineer's theory. Relatively large differences are observed. However, they decrease with increasing curvature radius and with incerasing quantity n of the Fourier expansion of the external load.